Effective management of refractory haematuria using PuraStat: A case report and literature review - J. Latham; K. Armstrong; A. Abdelrasheed; M. Shendy; B. Mohamed; T. Ellul (Urology Case Reports)
We report a case of refractory haematuria successfully managed using intravesical PuraStat®, a synthetic haemostatic agent primarily used in gastrointestinal bleeding. A 73-year-old male presented repeatedly with haematuria following bladder neck incision, unresponsive to conventional management. Application of PuraStat® via air cystoscopy resulted in complete haemostasis with no recurrence at two months. This case supports the expanding role of PuraStat® in urological bleeding where standard techniques fail.